Peningkatan Motivasi Dan Hasil Belajar Ipa Melalui Penerapan Strategi True Or False Dengan Media CD Interaktiv Pada Siswa Kelas V SD Negeri Godog 02 Tahun Ajaran 2014/2015 - WIJAYA, BANGUN, Dra. Risminawati, M.Pd (2015)
This study aims to improve motivation and learning result IPA in fifth grade students of Godog 02 Elementary Scool ,Polokarto, by Implementation True or False strategi through with CD Interactive media. This type of research is classroom action research (PTK). The subjects of this study were teachers (researcher) and fifth grade students Godog 02, amount to 16 students consisting of 13 male students and 3 female students. The analysis technique used is descriptive comparative technique by Interactive analysis which consists of collection, reduction, presentation, and conclusion. Research data shows increased in motivation and learning result IPA. Improvements can be seen in indicators in learning can increase in pree-cycle stages is 56, 25%, the first cycle is 81, 25%, and the second cycle by 87, 50%. Resilient in the face of adversity increased in stages pree-cycle is 43, 75%, first cycle is 75% and the second cycle is 81, 25%. Perseverance in the task increased in stages pree-cycle is 50%, the first cycle is 81, 25%, to second cycle 87, 50% . Hobby in problems solving incrased pree-cycle is 50%, the first cycle is 68.25%, then the second cycle is 75%. Learning result Students who have reached KKM also increased in pree-cycle stage is 37, 50%, the first cycle is 75%, then thes econd cycle 87, 50% .The conclusion of this study is that the implementation of the True or False Strategy and the use of Interactive CD media able to improve motivation and learning result IPA in fifth grade students Godog 02 years Doctrine 2014/2015.